PENGEMBANGAN BAHAN AJAR KIMIA UNSUR GOLONGAN VIIIA (GAS MULIA) DAN TOPIK KHUSUS ZEOLIT BERBASIS PBL - dea ayu tamara; Muhammad Hadeli L; Sanjaya sanjaya (Chemistry Education Study Program Sriwijaya University, 2022)
Research Development of group VIIIA and zeolite elemental chemistry teaching materials and problem based learning (PBL) aims to produce valid, practical and effective PBL-based teaching materials. This research is a development research with ADDIE development model combined with Tessmer formative evaluation. The stages of ADDIE development used in this study include the analysis stage, the design stage, and the development stage only, which then proceeds to the Tessmer formative evaluation stage which includes expert review, one to one, small group, and field test. At the expert review stage, PBL-based teaching materials were validated by experts from the field of pedagogic experts with an average score of 1 (high), material experts with an average score of 1 (high) and design experts with an average score of 0.933 (high). The results of the validation assessment scores obtained at the expert review stage were 0.978 (high). This shows that the PBL-based teaching materials that have been developed are valid. The practicality of PBL-based teaching materials is seen from the results of questionnaires and respondents' comments on PBL-based teaching materials with a Cronbach's Alpha value at the one to one stage of 0.800 (very high) and at the small group stage of 0.727 (high) which means PBL-based teaching materials have been practically developed. The effectiveness of the PBL-based teaching materials that have been developed can be seen from the learning outcomes test at the field test stage with an N-gain score of 0.84 in the high category. This shows that the PBL-based teaching materials that have been developed are effective. It can be that the PBL-based teaching materials that have been developed have met the valid, practical, and effective criteria.Keywords: Development research, Problem based learning (PBL) teaching materials, Elemental chemistry of group VIII A and zeolite.